2013
DOI: 10.1002/dys.1464
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics of Dyslexia: An Overview

Abstract: Dyslexia is a highly heritable learning disorder with a complex underlying genetic architecture. Over the past decade, researchers have pinpointed a number of candidate genes that may contribute to dyslexia susceptibility. Here, we provide an overview of the state of the art, describing how studies have moved from mapping potential risk loci, through identification of associated gene variants, to characterization of gene function in cellular and animal model systems. Work thus far has highlighted some intrigui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
141
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(152 citation statements)
references
References 120 publications
3
141
0
3
Order By: Relevance
“…Twin studies estimate the heritability of the disorder to be between 0.50 and 0.60 (e.g. Grigorenko, 2001; see also Carrion-Castillo, Franke, & Fisher, 2013;Carrion-Castillo et al, 2017;Ramus, 2013). It has also been convincingly demonstrated that environmental factors, in particular SES, play a large role in reading skills (Bowey, 1995;Fluss et al, 2009).…”
Section: Phonological Awarenessmentioning
confidence: 99%
“…Twin studies estimate the heritability of the disorder to be between 0.50 and 0.60 (e.g. Grigorenko, 2001; see also Carrion-Castillo, Franke, & Fisher, 2013;Carrion-Castillo et al, 2017;Ramus, 2013). It has also been convincingly demonstrated that environmental factors, in particular SES, play a large role in reading skills (Bowey, 1995;Fluss et al, 2009).…”
Section: Phonological Awarenessmentioning
confidence: 99%
“…Requires intensive follow-up studies to pinpoint etiological variants in regions of linkage. (Fisher and DeFries 2002) However it can sometimes be preferable to use quantitative measures to characterize affected individuals and their unaffected relatives, with the potential to also apply these across different related disorders, and even in unselected population cohorts (Carrion-Castillo et al 2013;Newbury et al 2014;Paracchini 2011). Quantitative measures circumvent problems arising from variations in diagnostic criteria.…”
Section: Phenotypes In Genetic Studies Of Languagementioning
confidence: 99%
“…A large number of subsequent studies have tested these candidate genes for association with affection status or with various psychometric measures, in cohorts with the same disorder as the original linkage cohort, or with the other of the two disorders (Carrion-Castillo et al 2013). Association with quantitative measures in general population cohorts has also been investigated (Paracchini et al 2008Scerri et al 2011).…”
Section: Stutteringmentioning
confidence: 99%
See 2 more Smart Citations